Your business and the law - Bowen, Jan. (St Leonards, NSW : Allen and Unwin, 1998)
Establishing a business: starting out; A partnership; Companies, trading trusts and joint ventures; Acquiring a franchise; Acquiring premises. Operating a business: legal documents; Consumer protection obligations; Unfair trading; Granting credit...
Keywords: Australia; Business; Law; Law and legislation; Small business; Small business -- Law and legislation -- Australia